Degradation of a Thin Ag Layer Induced by Poly(3,4ethylenedioxythiophene):Polystyrene Sulfonate in a Transmission Electron Microscopy Specimen of an Inverted Polymer Solar Cell - Suh, Youngjoon; Lu, Ning; Lee, Sang H.; Chung, Won-Suk; Kim, Kyungkon; Kim, BongSoo; Ko, Min Jae; Kim, Moon J. (American Chemical Society, 2012)
It was found that the Ag electrode layer in a transmission electron microscopy (TEM) specimen of an inverted polymer solar cell structure of Ag/PEDOT:PSS/P3HT:PCBM/TiO2/ITO/glass (where PEDOT is poly(3,4-ethylenedioxythiophene), PSS is polystyrene sulfonate, and ITO is indium tin oxide) was broken down into particles as time passed. In order to investigate the cause of Ag particle formation and the effect of the degradation on the performance of solar cells, the temporal change of the cross-sectional TEM micrographs was examined together with energy-dispersive Xray spectroscopy (EDS) analysis and electron tomography. Temporal degradation of Ag/Si and Ag/1 nm-Ti/PEDOT:PSS/ITO/glass structures was also studied. Absorption of water by the PEDOT:PSS layer followed by coriosion of the grain boundaries of the Ag layer by the corrosive water was thought to be the reason of Ag particle formation and fast performance lowering of the device.